Epigenetics in hepatocellular carcinoma. (November 2022) - Nagaraju, Ganji Purnachandra; Dariya, Begum; Kasa, Prameswari; Peela, Sujatha; El-Rayes, Bassel F.
Highlights: Hepatocellular carcinoma (HCC) is the most common primary liver cancer worldwide. The epigenetic alterations contribute to the differences in HCC genomes. The epigenetic effectors effect the chromatin structure and function of HCC. Epidrugs are promising therapeutic inhibitors for HCC progression. Abstract: Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver and has a high fatality rate. Genetic and epigenetic aberrations are commonly observed in HCC. The epigenetic processes include chromatin remodelling, histone alterations, DNA methylation, and noncoding RNA (ncRNA) expression and are connected with the progression and metastasis of HCC. Due to their potential reversibility, these epigenetic alterations are widely targeted for the development of biomarkers. In-depth understanding of the epigenetics of HCC is critical for developing rational clinical strategies that can provide a meaningful improvement in overall survival and prediction of therapeutic outcomes. In this article, we have summarised the epigenetic modifications involved in HCC progression and highlighted the potential biomarkers for diagnosis and drug development.